Effective Business Communications - Murphy, Herta A. and Hildebrandt, Herbert W. (New York McGraw-Hill, 1991)
This guidebook to communications both inside and between companies includes over 400 business examples. There are chapters on new technology, employment-related communication topics, business reports and international communications. Exercises and checklists are also provided.
Include References and Index
Keywords: Business communication -- Communication in management